Analisis Uji Petik Kopi Gelondong terhadap Kualitas Hasil Panen - Muhammad Thoriq Fauzan; Agief Julio Pratama (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
The acceptance sampling test of coffee cherries is an important quality control stage in Arabica coffee processing, yet operational evidence at the estate level remains limited. This study aimed to analyze the implementation of acceptance sampling for coffee cherries and to identify the proportions of normal and defective cherries as a basis for improving harvest quality. The research was conducted at an Arabica coffee estate in Situbondo by observing monthly harvest samples from April to August 2024 to classify cherry color (red, partially ripe, green, and black) and fruit density after soaking (partially empty, empty, single bean, and double bean). The results showed that the cherry composition consisted of 93.63% red, 3.54% partially ripe, 0.09% green, and 2.84% black cherries. The density test results indicated 4.30% partially empty cherries, 0.79% empty cherries, 10.27% single-bean cherries, 84.58% double-bean cherries, and 4.00% coffee berry borer-infested cherries. These findings indicate that acceptance sampling is useful for identifying harvest lots that do not meet quality standards and can serve as a basis for improving red cherry picking practices, harvest timing, and field supervision.